Salivary testosterone responses to a physical and psychological stimulus and subsequent effects on physical performance in healthy adults - Liam Kilduff (HORMONES, 2016)
OBJECTIVE: To address the rapid influence of testosterone (T) on neuromuscular performance, we compared the T and physical performance responses of adults exposed to a physical and psychological stimulus. DESIGN: A group of healthy men (n=12) and women (n=14) each completed three treatments using a randomised, crossover design: exercise involving five × ten-second cycle sprints, viewing a video clip with aggressive content and a control session. Salivary T concentrations, hand-grip strength (HGS) and countermovement jump peak power (CMJ PP) were assessed before and 15 minutes after each session. RESULTS: The relative changes in T (17±29%) and CMJ PP (-0.1±4.4%) following sprint exercise were superior to the aggressive video (-6.3±19%, -2.2±5.9%) and control (-4.8±23%, -2.8±4.4%) treatments, respectively (p ≤0.05). Pre-treatment T levels correlated (r= -0.58 to -0.61, p <0.05) with the T responses of men (sprint exercise) and women (sprint exercise, aggressive video), but no variables were significantly correlated with the relative changes in HGS or CMJ PP. CONCLUSIONS: Sprint exercise promoted a general rise in T and maintained CMJ PP, relative to the video and control treatments. In both sexes, those individuals with higher pre-test T levels tended to produce smaller T responses to one or more treatments. These data highlight the importance of stimulus selection and individual predispositions when attempting to acutely modify T and associated physical performance.